1989
DOI: 10.1123/jtpe.8.2.87
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research on Time in Sport Pedagogy

Abstract: This article provides a representative review of the current literature on time-related research in sport pedagogy. The reviewed studies are presented and discussed in four general areas: how time has been conceptualized, how time has been measured, what is known about how time is spent in physical education and sport settings, and what is still left to be known about time-related events. The final section suggests a six-item agenda for expanding and continuing research on time in sport pedagogy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
13

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 0 publications
2
24
1
13
Order By: Relevance
“…Their experiences reflect many of the topics that have been presented in the literature, (Meltzer, 1989;Rink, 1994;Silverman, 1985Silverman, , 1990Silverman et al, 1988;Silverman et al, 1995), skill progression, and how tasks are presented especially skill development, appropriate time and practice, and task presentation. This suggests that research on students' perception reinforces other types of physical education research and provides insight into how teachers and class structure impact student skill development and attitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their experiences reflect many of the topics that have been presented in the literature, (Meltzer, 1989;Rink, 1994;Silverman, 1985Silverman, , 1990Silverman et al, 1988;Silverman et al, 1995), skill progression, and how tasks are presented especially skill development, appropriate time and practice, and task presentation. This suggests that research on students' perception reinforces other types of physical education research and provides insight into how teachers and class structure impact student skill development and attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Time and appropriate practice is crucial for student success (Buck, Harrison, & Bryce, 1991;Meltzer, 1989;Silverman, 1985Silverman, , 1990Silverman, , 1993Silverman, , 2005Silverman, Subramaniam, & Woods, 1998;Simons-Morton, Taylor, Snider, & Huang, 1993). Students, who did not attain skill, often could not participate when placed in game-like situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In physical education, validity studies of an observation instrument have been most associated with measures of student achievement (Silverman & Buschner, 1990;Silverman, Devillier, & Ramirez, 1991). Schempp (1987) and Metzler (1989) have identified the two most frequently deployed observational instruments in the study of teaching physical education as-the Cheffers's Adaptation of Flander's Interaction Analysis System (CAFIAS; Cheffers, Mancini, & Martinek, 1980) and Academic Learning Time-Physical Education (ALT-PE; Metzler, 1979).…”
mentioning
confidence: 99%
“…On the other hand, the time students were active was less than 30% of total class time and the time they were engaged in motor appropriate activities was less than 15% (Godbout, Brunelle, & Tousignant, 1987). Therefore, research showed that academic learning time (time allotted in activities with high success rate) ranged between 10% (Metzler, 1989), 14.6% (LaMaster & Lacy, 1993 and 20% (Lacy, LaMaster & Tommaney, 1996) of total class time. Overall, researchers' findings on active learning time were inconsistent with curriculum recommendations (LaMaster & Lacy, 1993).…”
Section: Review Of Literaturementioning
confidence: 99%